MiR-1299 is regulated by KCNQ1OT1 and inhibits cervical cancer progression: MiR-1299 regulated by KCNQ1OT1 in cervical cancer - Yang, Qian; Fu, Jing; Wang, Min; Fang, Yuelan; Fu, Jian (Cellular and Molecular Biology, 2023)
Cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC) is the most common malignancy of the female genital tract. MiR-1299 serves as a tumor suppressor, while KCNQ1OT1 acts as an oncogene in multiple malignancies. This research was designed to investigate the impacts of miR-1299 and KCNQ1OT1 on CESC progression. The downstream target of miR-1299 and the underlying regulatory mechanism of KCNQ1OT1 action on miR-1299 were explored. RT-qPCR was applied for RNA expression detection in CESC tissues and cells. RNA immunoprecipitation, RNA pulldown and luciferase reporter assays were applied to evaluate the binding between molecules in CESC cells. Cell Counting Kit-8 and colony formation assays were used for the measurement of CESC cell viability and proliferation. Western blotting was utilized to measure levels of apoptosis-related in CESC cells. MiR-1299 was downregulated in CESC tissues and presented a negative correlation with KCNQ1OT1 expression. KCNQ1OT1 was directly bound to miR-1299 to negatively modulate miR-1299 expression in CESC cells. The proliferative ability of CESC cells was suppressed by miR-1299 overexpression and was facilitated by KCNQ1OT1 overexpression. CESC cells apoptosis was promoted by miR-1299 mimics and inhibited by KCNQ1OT1 overexpression. In addition, in in vivo studies, miR‐1299 overexpression rescued the effects of KCNQ1OT1 overexpression on CESC xenograft tumor growth. Finally, KCNQ1OT1 was bound to miR-1299 to upregulate PDPK1 expression in CESC cells. Collectively, miR-1299 was regulated by KCNQ1OT1 and inhibited CESC progression in vivo and in vitro, suggesting the tumor-suppressor role of miR-1299 for CESC.